2022
DOI: 10.3389/fonc.2022.834564
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Neutrophil-to-Lymphocyte Ratio as a Prognostic Biomarker in Unresectable or Metastatic Esophageal Cancer Patients With Anti-PD-1 Therapy

Abstract: BackgroundThe neutrophil-to-lymphocyte ratio (NLR) is an inflammatory index calculated by the absolute neutrophil count dividing the absolute lymphocyte count, and its prognostic role in esophageal cancer (EC) patients with anti-PD-1 therapy remains unclear.MethodsA total of 140 unresectable or metastatic EC patients receiving PD-1 inhibitor treatment were included from Jan 2016 to Mar 2020. Kaplan–Meier method and log-rank test were used for comparing overall survival (OS) and progression-free survival (PFS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
(29 reference statements)
3
12
1
Order By: Relevance
“…Previous researches revealed that high NLR level has been consistently linked to a worse prognosis in EC when patients were treated with either topical therapies or systemic chemotherapy ( 34 , 35 ). Our results, consistent with these researches ( 29 , 30 ), showed that a high baseline NLR was in line with inferior survival in ESCC receiving immunotherapy. Multivariate cox analysis indicated that baseline NLR was an independent prognostic indicator for both PFS and OS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous researches revealed that high NLR level has been consistently linked to a worse prognosis in EC when patients were treated with either topical therapies or systemic chemotherapy ( 34 , 35 ). Our results, consistent with these researches ( 29 , 30 ), showed that a high baseline NLR was in line with inferior survival in ESCC receiving immunotherapy. Multivariate cox analysis indicated that baseline NLR was an independent prognostic indicator for both PFS and OS.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that the survival of patients with low ECOG PS score significantly improved after anti-PD-1 therapy, and was therefore considered a significant prognostic indicator for PFS and OS. In accordance to our findings, patients with ECOG PS≥2 had poorer PFS and OS than those with ECOG PS ≤ 1 ( 30 ). Regarding treatment lines, we found that the PFS and OS of patients accepting first-line anti-PD-1 treatment were significantly longer than those accepting second-line or posterior treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reported cutoffs of pretreatment NLRs required to significantly stratify survival range from 3 to 7 in these studies, [11][12][13]18 and 3.84, 5.0 and 6.0 for unresectable advanced and recurrent esophageal cancer, although the reports [11][12][13] included patients with esophageal adenocarcinoma treated by some types of ICI or by combination chemotherapies. [27][28][29] The optimal cutoff for pretreatment NLRs required to significantly stratify the survival of patients with ESCC who underwent nivolumab monotherapy in the present study was 4.9. Our cutoff value of NLR was within the range for those of esophageal and other types of cancer.…”
Section: Discussionmentioning
confidence: 80%
“…The neutrophil-to-lymphocyte ratio (NLR) and the monocyte-to-lymphocyte ratio (MLR) are recognized as the hallmarks of systemic inflammatory status that can reflect the prognosis of ICIs-received solid tumors: non-small-cell lung cancer (NSCLC) [ 21 ], melanoma [ 22 ], and gastric cancer (GC) [ 23 , 24 ]. Recent research has looked into the prognostic value of inflammatory indicators in ESCC patients who have received the anti-PD-1 immunotherapy [ 25 , 26 , 27 ]. In their studies, patients in the second or later lines make up a large proportion.…”
Section: Introductionmentioning
confidence: 99%